Impact of Obesity in Hospitalized Patients with Heart Failure: A Nationwide Cohort Study. Issue 11 (November 2020) - Gajulapalli, Rama Dilip; Kadri, Amer; Gad, Mohamed; Chahine, Johnny; Nusairat, Leen; Rader, Florian
Abstract : Objectives: Obesity and cardiovascular disease remain significant burdens on the overall provision of health care in the United States. Obesity has been shown to be a direct risk factor for heart failure (HF). We conducted a nationwide cohort study to assess the short-term impact of obesity in hospitalized patients with HF. Methods: We identified 1, 520, 871 encounters with a primary diagnosis of HF in the 2013–2014 Nationwide Readmission Database. We excluded patients younger than 18 years (n = 2755), hospitalized patients discharged in December (n = 126, 137), patients with missing mortality information (n = 477), missing length of stay (LOS; n = 91), patients who were transferred to another hospital (n = 38, 489), and patients with conflicting body weight information (n = 7757). Multivariable logistic regression was used to evaluate the association between baseline characteristics (including the presence of obesity) and in-hospital mortality, as well as 30-day readmission rates. Results: The overall in-patient mortality rate was 2.8% (n = 37, 927). Obese patients had numerically a lower mortality (1.8%) compared with the nonobese patients (3.1%); however, the difference in risk was not significant on multivariable analysis (hazard ratio 0.97, 95% confidence interval 0.94–1.01). In the overall cohort, 20.6% (n = 269, 988) were readmitted within 30 days. The risk of 30-day readmission was significantly lower in obese patients (19.4%) compared with nonobese patients (20.9%) (odds ratio 0.85, 95% confidence interval 0.84–0.86). Obese patients had longer LOSs (median of 5 days [3–7] vs 4 days [2–6], P < 0.001) and higher costs of index admission (median of $27, 206 [$16, 027–$48, 316] vs $23, 339 [$13, 698–$41, 982], P < 0.001) compared with nonobese patients. Conclusions: In this cross-sectional study of patients hospitalized for HF in the United States, obesity was not associated with a higher risk of inpatient mortality, but it was associated with a lower 30-day readmission rate. Obese patients with HF, however, had longer LOSs and higher costs of index admission. Our findings support the obesity paradox seen in patients with HF. Abstract : Obesity and cardiovascular disease remain a significant burden on the overall provision of health care in the United States. Obesity has been shown to be a direct risk factor for heart failure. It is, however, unclear what effect obesity plays directly in the morbidity of patients hospitalized with congestive heart failure. We performed a large cohort study regarding the short-term outcomes of obese patients admitted to the hospital with acute congestive heart failure. We found that subjects identified as obese did not have a higher risk of inpatient mortality, and in fact, had lower 30-day readmission rates compared with nonobese subjects. Obesity, therefore, does not seem to be related to worse outcomes in terms of mortality or readmissions, but it does lead to longer length of stay as well as higher cost of admission.